Unlocking the evolution of abdominal specializations in Luciuranus fireflies (Coleoptera, Lampyridae). (16th September 2022) - Silveira, Luiz; Souto, Paula; Khattar, Gabriel; Takiya, Daniela M.; Nunes, Viviane; Mermudes, José Ricardo M.; Monteiro, Ricardo; Macedo, Margarete
Abstract: Understanding the evolution of genitalic traits and their co‐evolution between sexes is at the core of Evolutionary Biology. Cross‐species reproductive trait co‐variation can be the outcome of hybrid avoidance and/or sexual selection. Although the outcome of these two phenomena will look similar, they yield distinct patterns of species co‐occurrence. Partial or complete syntopy—but not allopatry—among species is expected to lead to hybrid avoidance strategies. Conversely, sexual selection is involved in genitalic evolution regardless of co‐occurrence with closely related species. The genus Luciuranus Silveira, Khattar & Mermudes, 2016 includes eight species of fireflies endemic to the Atlantic forest. Among these, five feature species‐specific morphology of the male and female terminalia suggest a clamping mechanism, while the remaining three species have similar terminalia across species. The evolutionary history of Luciuranus and its putative clamping mechanism remains unknown. Furthermore, the female internal morphology, which could provide insight into the biology of these poorly known fireflies, was never studied. Here, we combine morphology (55 characters) and DNA sequences ( COI, 16S ) and analyse them through probabilistic criteria to provide the first total evidence phylogeny of Luciuranus . We show that the acquisition of the abdominal modifications in Luciuranus was stepwise, becoming increasingly more complex. Moreover, maximum likelihood‐based ancestral state reconstructions show that male terminalia co‐evolved with female abdominal morphology in Luciuranus . Given the total allopatry among species, it is likely that lineage‐specific sexual selection on mating behaviour, instead of hybrid avoidance through natural selection, has shaped the unique abdominal morphologies of Luciuranus species.